Characterization Of Two Chalcone Derivatives Isolated From Finger Root With Nutraceutical Potentials - Mohammed, Ibrahim Awad; Akhtar, Muhammad Nadeem; Abdullah, Hussam Dawood; Hazrulrizawati, Hamid (IJAR, 2018)
Boesenbergia rotunda is an example of medicinal herbal plants which has been traditionally employed in the treatment of many life-threatening ailments such as diuretic, dysentery, inflammation, aphrodisiac and gastrointestinal disorder.In this study the two chalcone derivatives were isolated from the root of B. rotunda using column-thin chromatography and characterized using different spectroscopy methods such as such as UV-VIS, FTIR, and 1HNMR. The bioactive compound identified were pinostrobin chalcone (1) and cardamone (2). These IR spectra, UV-vis photometry analysis and 1HNMR suggested that the chemical constituent isolated to be a flavonoid derivative, which is similar to the previous studies. The result of the study suggests that B. rotunda rhizome has a potential in drug and nutraceutical applications.